Willingnes to Pay Sungai Tamban Muara Kecamatan Tamban Kabupaten Barito Kuala - Noor, Raisa (PPJP ULM, 2018)
Raisa Noor, a Willingness to Pay Tamban River Estuary Barito Kuala Regency TambanSubdistrict. Under the guidance of Yunita Sopiana, SE, MSE.The purpose of the research is (1) find out the assessment of the communityaround the River toward the assessment mouth of the river ecosystem State TambanBarito Kuala Regency Tamban Subdistrict. (2) knowing the value of the community’swillingness to pay (willingness to pay) for the benefit of the river ecosystem TambanEstuary.This research is descriptive qualitative research using primary and secondarydata are data from the office of the Chief of the village Tamban, in the form ofquestionnaires and so forth.The result of the community assessment and quality conditions of the Riverestuary Tamban declined. Although river water is unfit for consumption, some people stilldepend on river water Tamban Estuary. The River Estuary u.s Tamban watertransportation is already limited. Poor water quality of the River Estuary Tamban ismainly caused by industrial activity and high his intensive use u.s water transportation.The occurrence of shifting values and water quality of the River Estuary Tamban, in theend, make an unhealthy environment for the people that use river water Tamban Estuary.Particularly the communities along the river basin Jl based the calculation od derivedCommunity willingness to pay ( willingness to pay) from the mouth of the river ecosystemTamban is amounting to Rp. 133,040,000,-. The result from the Division of the total WTPand the number of the population the average WTP of this Idr 80.000 per head of thefamily.